2021
DOI: 10.1101/2021.05.26.445882
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Abundant and rare bacterial taxa structuring differently in sediment and water in thermokarst lakes in the Yellow River Source area, Qinghai-Tibet Plateau

Abstract: Thermokarst lakes are forming from permafrost thaw and severely affected by accelerating climate change. Sediment and water in these lakes are distinct habitats but closely connected. However, our understanding of the differences and linkages between sediment and water in thermokarst lakes remain largely unknow, especially from the perspective of bacterial community patterns and underlying mechanisms. In this study, we examined bacterial communities in sediment and water in thermokarst lakes in the Yellow Rive… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 77 publications
(112 reference statements)
0
1
0
Order By: Relevance
“…Only two studies have reported bacterioplankton in lake waters within YRH. Previous research found that the bacterial communities in water have a significant correlation with water conductivity, total nitrogen, and total phosphorus in the thermokarst lakes from the YRH region (Ren et al, 2021a).…”
Section: Introductionmentioning
confidence: 90%
“…Only two studies have reported bacterioplankton in lake waters within YRH. Previous research found that the bacterial communities in water have a significant correlation with water conductivity, total nitrogen, and total phosphorus in the thermokarst lakes from the YRH region (Ren et al, 2021a).…”
Section: Introductionmentioning
confidence: 90%